Microwave vs. reflux synthesis of bis-thiourea derivative: yield optimization, crystallographic understanding and optical sensing potential - Hasanain Salah Naeem,; Jaber, Israa; Suhaila Sapari,; Fazira Ilyana Abdul Razak,; Rudaini, Bilal Majid; Nurul Hidayah Abd Razak,; Asmaa, Soheil Najm; Siti Aishah Hasbullah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
A new bis-thiourea (BT) derivative was successfully synthesized using both conventional reflux and microwave irradiation methods. The microwave irradiation reaction yielded a greater percentage yield of 73%, while the reflux heating yielded only 44%. The microwave irradiation procedure takes a minimum of 10 min to complete, in contrast to the reflux heating method, which takes 24 h. The compound was characterised using a variety of spectroscopic techniques, including UVVis, FTIR, nuclear magnetic resonance (1 H-NMR and 13C-NMR), and single crystal X-ray crystallography (XRC). It shows that BT has a high ability to form hydrogen bonds of both intermolecular and intramolecular types, as demonstrated by X-ray crystallography and DFT calculations. In addition, this research provides insights into the possible uses of BT in coordination chemistry involving metal ions, such as a copper ions. Through the use of density-functional theory (DFT) and UV-Vis investigations, it is envisaged that the BT compound has a strong tendency to form stable copper ion complexes. This is supported by the optimal energy value E(UB3LYP) observed for the Cu(II) complex.